2016
DOI: 10.1016/j.aat.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Supreme and the ProSeal laryngeal mask airway in patients undergoing laparoscopic cholecystectomy: A randomized controlled trial

Abstract: The LMA ProSeal has a higher OLP than the LMA Supreme. The success rate of first attempt insertion and ease of insertion were better for the LMA Supreme group and the insertion time was lower in the LMA Supreme group. The Supreme and ProSeal LMAs were both effective for positive pressure ventilation in laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…OPLP observed in our study was similar to the values noted in earlier studies. 5,9,[14][15][16] There have been many studies comparing PLMA with other SADs like LMA-Supreme and Igel 17,[18][19][20] They have found that both of these devices are suitable alternatives in laparoscopic surgeries, but PLMA has higher OPLP compared to other SADs. Therefore PLMA may be the most suited device for laparoscopic surgeries among SADs.…”
Section: Discussionmentioning
confidence: 99%
“…OPLP observed in our study was similar to the values noted in earlier studies. 5,9,[14][15][16] There have been many studies comparing PLMA with other SADs like LMA-Supreme and Igel 17,[18][19][20] They have found that both of these devices are suitable alternatives in laparoscopic surgeries, but PLMA has higher OPLP compared to other SADs. Therefore PLMA may be the most suited device for laparoscopic surgeries among SADs.…”
Section: Discussionmentioning
confidence: 99%
“…Airway pressure is an important parameter for intraoperative monitoring of airway resistance. Excessive airway resistance can cause ventilator-associated lung injury [24]. Laparoscopic surgery is characterized by short surgical duration, minimal trauma, and rapid recovery; however, pneumoperitoneum may cause unpredictable changes in respiratory function [25].…”
Section: Discussionmentioning
confidence: 99%
“…However, the difference in our study may be of little clinical relevance as the pressures in the both groups were within clinically acceptable range and comparable to oropharyngeal seal pressure seen with various studies using PLMA for airway management in patients undergoing laparoscopic cholecystectomy. [516171819]…”
Section: Discussionmentioning
confidence: 99%
“…[212223] Galgon et al also found a lesser time required to achieve a clinically adequate airway in whom Air-Q was inserted in contrast to those in whom PLMA was inserted (Air-Q 20 ± 14 seconds; PLMA 28 ± 11 seconds). [16] The longer time in their study to insert PLMA may be related to additional step of use of laryngoscopy prior to insertion of PLMA railroaded over the gum elastic bougie. [17] Furthermore, the different device characteristics of AQB in contrast to the Air-Q may be the contributing factor for longer time of insertion in our study in contrast to the study by Galgon et al…”
Section: Discussionmentioning
confidence: 99%